Scholarship of schoolteachers in Peru: an experience of public-private collaboration, beyond the University Social Responsibility - Ruiz De Castilla, Inés (2018)
The current university organizations have assumed responsibility for the connection between the university and society and promote the process of public-private agreements, as developed between the Pontifical Catholic University of Peru (PUCP) and the National Scholarship and Educational Credit Program (PRONABEC) of the Government of Peru, in order to promote, and develop, their experience in the training of teachers of the Public School Magisterial in order to improve the teaching performance and the quality of learning in students.This article presents some guidelines developed during the execution of the President of the Republic Scholarship (2014-2015) and which in various ways explain the vocation of service and commitment to educational development, which PUCP has been carrying out since its founding as a university institution.In this regard, the University devoted resources and resources beyond what was agreed in the signed agreements, assuming the mission as a proper process of University Social Responsibility (USR) in a positive experience that far exceeded the expectations projected for the benefit of educational quality of teachers and students of the country.